2012
DOI: 10.1186/1471-2407-12-395
|View full text |Cite
|
Sign up to set email alerts
|

RON is not a prognostic marker for resectable pancreatic cancer

Abstract: BackgroundThe receptor tyrosine kinase RON exhibits increased expression during pancreatic cancer progression and promotes migration, invasion and gemcitabine resistance of pancreatic cancer cells in experimental models. However, the prognostic significance of RON expression in pancreatic cancer is unknown.MethodsRON expression was characterized in several large cohorts, including a prospective study, totaling 492 pancreatic cancer patients and relationships with patient outcome and clinico-pathologic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Moreover, aberrant RON signaling serves as a mechanism for acquired chemoresistance. However, RON expression in correlation with clinicopathophysiologic parameters has not been fully established (11). Thus, further investigation is required to demonstrate the pathogenic role of RON in PDAC malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aberrant RON signaling serves as a mechanism for acquired chemoresistance. However, RON expression in correlation with clinicopathophysiologic parameters has not been fully established (11). Thus, further investigation is required to demonstrate the pathogenic role of RON in PDAC malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only a single study has been published: Tactacan et al (31) assessed RON expression in a total of 492 pancreatic cancer patients and evaluated the association between RON expression and patient outcomes and clinicopathological variables. The study identified that increased RON expression was a biomarker for poor prognosis in a training set.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that RON mediates several oncogenic functions in cancer cells, including cell proliferation and survival; cell adhesion and spreading; cell dissociation and migration; EMT and matrix invasion; and establishment of metastasis. These features point to the importance of RON in later stages of cancer and RON expression correlates strongly with invasion, tumor stage, and poor prognosis in most, but not all, cancers (Ronsin et al 1993;Wang et al 2003Wang et al , 2006Lee et al 2005;O'Toole et al 2006;Thomas et al 2007;Welm et al 2007;Catenacci et al 2011;Benight and Waltz 2012;Song et al 2012;Tactacan et al 2012).…”
Section: Signaling Pathways Downstream From Ron In Cancer Progressionmentioning
confidence: 99%